Fairyland : in art and poetry - Lach, William, 1968-; Doyle, Richard, 1824-1883 (New York : Metropolitan Museum of Art/H. Holt, 2001)
Illustrations by Richard Doyle accompany poems by various authors from different eras to describe a land of fairies and magic.
4.9
3-6
3-6
Keywords: Fairy poetry, English; Fairy poetry, American; Fairies in art; Fairies -- Poetry; Fairies -- Poetry